Risk stratification and clinical course of hepatitis B virus reactivation in rheumatoid arthritis patients with resolved infection: final report of a multicenter prospective observational study at Japanese Red Cross Hospital - Wataru Fukuda; Tadamasa Hanyu; Masaki Katayama; Shinichi Mizuki; Akitomo Okada; Masayuki Miyata; Yuichi Handa; Masatoshi Hayashi; Yoshinobu Koyama; Kaoru Arii; Toshiyuki Kitaori; Hiroyuki Hagiyama; et al. (Arthritis Research & Therapy, 2019)
Abstract Background The prophylaxis for hepatitis B virus (HBV) reactivation assumes that hepatic injury after reactivation is often rapidly progressive and can evoke fulminant hepatitis. The incidence and prognosis of reactivation in patients with rheumatoid arthritis (RA) may be different from those receiving organ transplantation and cancer chemotherapy. This study aimed to investigate the incidence, risk factors, and clinical course of HBV reactivation and develop a scoring system for risk stratification in RA patients with resolved infection. Methods HBV DNA was measured using real-time polymerase chain reaction, and patient data were collected for 4 years in RA patients with resolved HBV infection who were treated with steroids or synthetic or biologic immunosuppressive drugs. Results Among 1127 patients, HBV DNA was detected in 57 patients (1.65/100 person-years); none of the reactivated patients exhibited worsening of hepatic function. Multivariate logistical analysis revealed that age > 70 years and HB core antibody (HBcAb) positivity alone were independent risk factors for HBV reactivation. HBV DNA ≥ 2.1 log copies/mL was observed in 15 patients (0.43/100 person-years); seven patients were treated with nucleic acid analogs (NAAs), whereas the remaining eight were observed without treatment. Among reactivated cases, 15 cases changed to HBV DNA-negative status spontaneously, whereas 24 cases remained HBV DNA positive < 2.1 log copies/mL during the observation period. We designed the following scoring system: HBV reactivation risk score = 1 × (age > 70 years) + 2 × (HBcAb positivity alone) + 1 × (treatment other than methotrexate monotherapy). This revealed that patients with the highest score had an odds ratio of 13.01 for HBV reactivation, compared to those with the lowest score. Conclusions Rapid progression and poor outcomes after HBV reactivation were not frequent in RA patients with resolved infection. Our new risk scoring system might be useful for screening and optimization of prophylactic treatment by distinguishing patients with significantly lower reactivation risk.